2003
DOI: 10.1101/gr.377203
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Analysis of Genetic Alterations in Small DNA Samples Using Hyperbranched Strand Displacement Amplification and Array–CGH

Abstract: Structural genetic alterations in cancer often involve gene loss or gene amplification. With the advent of microarray approaches for the analysis of the genome, as exemplified by array–CGH (Comparative GenomicHybridization), scanning for gene-dosage alterations is limited only by issues of DNA microarray density. However, samples of interest to the pathologist often comprise small clusters of just a few hundred cells, which do not provide sufficient DNA for array–CGH analysis. We sought to develop a simple met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
213
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(237 citation statements)
references
References 57 publications
20
213
4
Order By: Relevance
“…Similar effects were reported with the mutant single-strand binding protein protein of Thermus thermophilus (Inoue et al, 2006). One report suggested that background synthesis from primerprimer interactions may also be reduced or eliminated by the modification of hexamer primers with the incorporation of one or two 5 0 -terminal universal bases (Lage et al, 2003). Recent work demonstrated that carefully avoiding trace levels of DNA contamination resulted in only 0.36-1.0% of sequences being nonspecific (Marcy et al, 2007a).…”
Section: A Brief History Of Mdasupporting
confidence: 48%
“…Similar effects were reported with the mutant single-strand binding protein protein of Thermus thermophilus (Inoue et al, 2006). One report suggested that background synthesis from primerprimer interactions may also be reduced or eliminated by the modification of hexamer primers with the incorporation of one or two 5 0 -terminal universal bases (Lage et al, 2003). Recent work demonstrated that carefully avoiding trace levels of DNA contamination resulted in only 0.36-1.0% of sequences being nonspecific (Marcy et al, 2007a).…”
Section: A Brief History Of Mdasupporting
confidence: 48%
“…Links to genomic databases helped to identify candidate genes for further investigation. A small number of published studies applied aCGH technology to breast cancer cells, but only to a very limited extent (Pinkel et al, 1998;Albertson et al, 2000;Kauraniemi et al, 2001;Hyman et al, 2002;Pollack et al, 2002;Lage et al, 2003). Almost all of these utilised a significantly smaller number of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of these utilised a significantly smaller number of specimens. Some of them focused only on cell lines (Hyman et al, 2002;Lage et al, 2003) or on individual chromosomes (Pinkel et al, 1998;Albertson et al, 2000;Kauraniemi et al, 2001). We are not aware of any published reports on array or conventional CGH analysis of DNA abnormalities in irradiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] In all, 10 ng of BAC DNA (1 ml) was added to 9 ml of the sample buffer before the mixture was incubated at 951C for 3 min and then cooled on ice for 5 min. In all, 10 ml of f29 polymerase reaction mix (1 ml of f29 polymerase in 9 ml of reaction buffer) was added, and the mixture was then incubated at 301C for Z16 h. To inactivate the enzyme the mixture was heated for 10 min at 651C.…”
Section: Bac Dna Amplificationmentioning
confidence: 99%